Effect of postharvest storage of whole fruit on physico-chemical and microbial changes of fresh-cut cantaloupe (Cucumis melo L. reticulatus cv. Glamour) - Zainal Abidin, Munira; Shamsuddin, Rosnah; Othman, Zaulia; Abdul Rahman, Russly (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Cantaloupes continue to ripen after harvesting which is caused by ethylene production due to climacteric behaviour during postharvest storage. In this study, the cantaloupe fruits harvested at commercial maturity were evaluated for quality attributes during three weeks of storage at 10°C and a relative humidity (RH) of 90±5%. In addition, fresh-cut samples were stored for a further 19 days at 2°C and 87% RH. The fresh-cut samples were prepared on a weekly basis by dipping into deionised water (control) at 2°C for 1 minute. The effect of postharvest storage of cantaloupe on the physico-chemical properties and microbial activity was observed prior to fresh-cut processing. It was found that firmness, luminosity (L*), and titratable acidity (TA) decreased, while total soluble solids (TSS), pH, TSS:TA ratio, microbial activity (total plate count (TPC) and yeast and mould (YM)) of the fresh-cut increased over the postharvest storage period of the fruit. Meanwhile, the orange colour and the intensity (hue angle, hab, and chromaticity) of the flesh did not differ significantly during storage. The cantaloupe stored for three weeks at a low temperature indicated a successful potential for fresh-cut processing due to good maintenance of the product quality.